B-Cell Activating Factor as a Cancer Biomarker and Its Implications in Cancer-Related Cachexia - Rihacek, Michal; Bienertova-Vasku, Julie; Valik, Dalibor; Sterba, Jaroslav; Pilatova, Katerina; Zdrazilova-Dubska, Lenka (BioMed research international, 2015)
B-cell activating factor (BAFF) is a cytokine and adipokine of the TNF ligand superfamily. The main biological function of BAFF in maintaining the maturation of B-cells to plasma cells has recently made it a target of the first FDA-approved selective BAFF antibody, belimumab, for the therapy of systemic lupus erythematosus. Concomitantly, the role of BAFF in cancer has been a subject of research since its discovery. Here we review BAFF as a biomarker of malignant disease activity and prognostic factor in B-cell derived malignancies such as multiple myeloma. Moreover, anti-BAFF therapy seems to be a promising approach in treatment of B-cell derived leukemias/lymphomas. In nonhematologic solid tumors, BAFF may contribute to cancer progression by mechanisms both dependent on and independent of BAFF's proinflammatory role. We also describe ongoing research into the pathophysiological link between BAFF and cancer-related cachexia. BAFF has been shown to contribute to inflammation and insulin resistance which are known to worsen cancer cachexia syndrome. Taking all the above together, BAFF is emerging as a biomarker of several malignancies and a possible hallmark of cancer cachexia.
Keywords: B-lymfocyty; Antibodies, Monoclonal; B-Cell Activating Factor; Biomarkers, Tumor; monoklonální protilátky; humanizované monoklonální protilátky; lidé; systémový lupus erythematodes; Antibodies, Monoclonal, Humanized; kachexie; Cachexia; Multiple Myeloma; mnohočetný myelom; nádorové biomarkery; faktor aktivující B-buňky; Lupus Erythematosus, Systemic; B-Lymphocytes; Humans